Development of MolGrid (Molecule Grid) on Molecular Shape Topics Based on VSEPR Theory - Syarifah Uyun Ehya; Erlina; Maria Ulfah (Universitas Pendidikan Mandalika, 2026)
Molecular geometry is a chemistry topic which often perceived as difficult by students because of its abstract nature. This study was completed to develop MolGrid (Molecule Grid), a digital puzzle-based learning media on molecular geometry based on VSEPR theory, and to determine its validity and students’ responses. The study obtained a Research and Development approach along with the ADDIE model. It is limited into the analysis, design, and development steps. The product was validated by two content experts and two media experts and tested on Grade XII students of SMA Negeri 5 Pontianak. Data collection was performed by utilizing validation sheets and student responses through the questionnaire. The results revealed the validity of the content reached 100% and media validity reached 98.61%, both categorized as highly valid. Students’ responses in the initial and main trials obtained average scores of 91.41% and 88.18%, respectively, which fall into the very good category. These findings indicate that MolGrid is highly valid and well received and is therefore suitable for a moleculare shape learning media.